Choice of Patient-Reported Outcome Measures for Midterm Assessment After Anterior Cruciate Ligament Reconstruction Surgery. Issue 8 (July 2022) - Webster, Kate E.; Klemm, Haydn J.; Feller, Julian A.
Background: Patient-reported outcome measures (PROMs) have become increasingly popular for assessing subjective elements of a patient's condition. Two frequently used knee-related PROMs after anterior cruciate ligament reconstruction (ACLR) surgery are the International Knee Documentation Committee Subjective Knee Form (IKDC-SKF) and the Knee injury and Osteoarthritis Outcome Score (KOOS). However, completing the full versions of both measures represents a considerable responder burden. Purpose: To compare a variety of KOOS short forms with each other as well as the IKDC-SKF in a large sample of ACLR patients between 2 and 6 years after surgery. Study Design: Cohort study (Diagnosis); Level of evidence, 2. Methods: The KOOS and IKDC-SKF were administered between 2 and 6 years (mean, 3 years) after ACLR surgery to a cohort of 832 patients (men, n = 489; women, n = 343). Two single-item assessment numerical evaluations were also completed for knee function and satisfaction. The following short form versions were calculated from the full KOOS: the KOOS-12 short form, KOOS–Physical Function Short form (KOOS-PS), KOOS–Joint Replacement Short form (KOOS-JR), and KOOS–Global. Descriptive statistics were calculated for all PROMs and associations between measures were explored using nonparametric (Spearman rho) correlations. Floor or ceiling effects were considered present if >15% of patients reported the worst (floor effect) or best (ceiling effect) possible score. Age and sex comparisons were also made for each PROM. Results: Ceiling effects were present for all KOOS short form versions. They were highly evident for the KOOS-JR and KOOS-PS (37%-44%), but they were only marginally above the threshold for the KOOS-12 and KOOS–Global (16%). The KOOS-12 and KOOS–Global had the highest correlation with the IKDC-SKF but only explained 58% to 59% of the variance in scores. The KOOS-12 and KOOS–Global were very highly correlated (ρ = 0.98). Only moderate correlations were seen between the single-item assessments and the IKDC-SKF or various KOOS short forms. There was a negligible association between patient age and PROM scores, but there was no significant sex difference for any of the PROMs. Conclusion: The IKDC-SKF together with either the KOOS–Global or KOOS-12 may provide a comprehensive range of knee-related PROMs with minimized responder burden at 2 to 6 years after ACLR.